2000
DOI: 10.17161/ch.vi1.11962
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of Parotoid Gland Secretions From Toads of the Genus Bufo

Abstract: Freeze-dried parotoid gland secretions from toads of the genus Bufo contained large proportions of protein (25-35% by weight). SDS-PAGE suggested that secretions from several species of Bufo contained mixtures of proteins in the relative molecular mass range of approximately 12 - 200 kDa, which exhibited markedly different banding patterns from species to species. These proteins were presumably not discovered before because the previous extraction procedures used with these secretions were designed to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…While the secretory granules occupying the lumen of poison glands in thumb pads were PAS and AB‐negative, they gave a positive reaction to bromphenol blue. These results supports the findings that these glands contain proteinaceous secretion and the secretion of poison glands are the source of some biologically active protein and peptide materials (Dapson et al, 1973; Perry, 2000). On the other hand, the secretion granules in the cytoplasm of secretory cells belonging to mucus glands were bromphenol blue‐negative and PAS‐positive.…”
Section: Discussionsupporting
confidence: 88%
“…While the secretory granules occupying the lumen of poison glands in thumb pads were PAS and AB‐negative, they gave a positive reaction to bromphenol blue. These results supports the findings that these glands contain proteinaceous secretion and the secretion of poison glands are the source of some biologically active protein and peptide materials (Dapson et al, 1973; Perry, 2000). On the other hand, the secretion granules in the cytoplasm of secretory cells belonging to mucus glands were bromphenol blue‐negative and PAS‐positive.…”
Section: Discussionsupporting
confidence: 88%
“…Literature analysis concerning the poison of bufonid parotoids, brings evidence that proteins, despite occurring in considerable amounts in the poison, have never received as much attention as the other compounds. Studies have shown that 25 to 35% of the dry weight of toad paratoid poison is represented by proteins [ 14 , 15 ]. However, the identity and actual function of this category of molecules in bufonid poison is still quite controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the large size of the individual glands that compose the parotoids, these cutaneous organs can synthesize and store significant large amounts of poison used in chemical defence against predators [ 3 , 5 ]. In toads in general, the secretion is composed of a mixture of steroids, biogenic amines and proteins, as well as mucus [ 3 , 5 , 10 , 14 , 15 ]. If ingested, toad skin secretion may cause death of several vertebrates, including humans [ 16 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These variations indicated that some proteins are species specific and their molecular mass varied according to the isolated granular intake in the same species. For Perry [31], the parotoid gland secretions from Amietophrynus mauritanicus (former Bufo mauritanicus) and Epidalea calamita (former Bufo calamita) are a mixture of proteins with the relative molecular mass range of approximately 12-200 kDa, and these proteins markedly exhibited different banding patterns according to the species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations on cutaneous molecules of Bufo gargarizans (former Bufo andrewsi) have shown some bioactive proteins, as protease inhibitor and lysozyme [8]. Moreover, Perry [31] suggested that the analysis of the protein profile could be used to taxonomic and evolutionary studies, helping species identification, particularly where anatomical criteria are Immunohistochemical results showed the Pgp expression in the glandular portion cells of the mixed and small granular glands, in the myoepithelial cells, as well as in some cells in the spongious dermis. The Pgp immunolabeling in the bufonid integument suggests that this protein may be involved with the extrusion of cytotoxic compounds.…”
Section: Discussionmentioning
confidence: 99%